Use of autoclaved aerated concrete particles for simultaneous removal of nitrogen and phosphorus as filter media from domestic wastewater. Issue 23 (14th October 2020) - Bao, Teng; Yu, Zhi Ming; Damtie, Mekdimu Mezemir; Wu, Ke; Jin, Jie; Zhang, Yong; Wei, Xing Lai; Frost, Ray L
ABSTRACT : In this study, autoclaved aerated concrete particles (AACPs) from construction waste were used to simultaneously remove phosphorus and nitrogen in biological aerated filters (BAFs). The effects of air/water (A/W) ratio on the removal performance of phosphorus (PO4 3− ), total organic carbon, total nitrogen (TN), and ammonia nitrogen were investigated. Results showed that AACP BAF was more efficient than commercially available ceramsite (CAC) BAF. For example, the removal rates of TN with AACP and CAC were 45.96% and 15.64%, respectively, and those of PO4 3− with AACP and CAC were 72.45% and 33.97%, respectively, at the A/W ratio of 3:1. Different characterization methods were utilized to evaluate the surface shape, elemental compostion, and internal and surface structure of AACP. The interconnectivity and uniformity of pores and the rough surface of AACP were found to be suitable for the growth of microbial biofilm. In addition, the growth of internal pores in AACP promoted the removal of phosphorus and nitrogen. The surface of used AACP contained a small amount of irregular crystals and was covered with a layer of aggregates, which were characterized as hydroxyapatite [HAP, Ca5 (OH)(PO4 )3 ]. The formation of HAP as a final byproduct confirmed the successful removal of phosphorus. Therefore, construction wastes, such as AACPs, could be recycled and utilized as a promising biofilter media for excellent wastewater treatment. GRAPHICAL ABSTRACT: UF0001